Neuromatous hyperplasia of the main bile duct in Von Recklinghausen disease: About a case - Machado, Fernando; Andreoli, Gustavo; Otero, Marta; Fernández, Roxana; Caviglia, Pablo; Silva, Celso; Torterolo, Edgardo (Cirugía del Uruguay, 1997)
The authors examine the clinic history of a woman with a Van Recklinghausen disease who had an asymptomatic neoplasic obstruction of the bife duct found during an open urgency cholecistectomy.